Wallago attu (Bl.) and its Parasitic Monogenea Mizelleus indicus (Jain, 1957), Pandey et al., 2003: A Model Towards Histopathological Studies for Host Parasite Interaction - Arya, Priya Vrat; Singh, Hridaya Shanker (Asian Journal of Biological and Life Sciences, 2020)
Host Parasite model study essentially reflect cruelty of parasite on the host through various means depending upon the site and degree of infection. Gill parasitic monogenea presents an excellent opportunity to look this in much more closer and specific way. Wallago attu (Bl.) was studied for histopathological damage caused by parasitic monogenea Mizelleus indicus (Jain, 1957), Pandey et al., 2003. During the extensive study spread over three year, control and infected gills well examined through scanning electron microscopy (SEM) as well as light microscopic tools. The damage caused on the gills as observed on several occassions have been self explanatory for the decline in fish health under heavy infection. Observations made during the study were coroborated with known studies and discussed in detail.
Keywords: Gill Parasite; histopathology; Host-Parasite Model; Microscopy; Mizelleus indicus; Monogenea